Diplomatic Appointments and Competency Standards in Indonesia: A Siyasah Dauliyah Analysis of Meritocracy and Ambassadorial Selection - Marha Awanis Syamlina; Muhammad Asro; Lutfi Fahrul Rizal; Tarmidzi Tarmidzi (Borneo International Journal of Islamic Studies, 2026)
The appointment of ambassadors is crucial to a state's diplomatic effectiveness and representation in international forums. In Indonesia, the appointment of non-career diplomats to strategic ambassadorial positions has raised concerns regarding compliance with meritocratic governance and competency requirements. This study examines whether Indonesia's regulatory framework governing diplomatic appointments adequately ensures diplomatic competence and aligns with the principles of Siyasah Dauliyah. Employing normative legal research, the study uses statutory, conceptual, and comparative approaches to analyze the 1945 Constitution, Law No. 37 of 1999 on Foreign Relations, Law No. 5 of 2014 on State Civil Apparatus, and Presidential Regulation No. 56 of 2021. The findings reveal that the existing framework grants broad discretion over ambassadorial appointments while lacking measurable, enforceable competency standards. This gap weakens the implementation of merit-based governance and may affect diplomatic effectiveness. Drawing on the principles of amanah (trustworthiness), kifayah (competence), and 'adalah (justice), this study proposes an integrated evaluative framework for diplomatic appointments. It argues that legal reform is necessary to establish objective competency benchmarks and transparent selection mechanisms for both career and non-career diplomats.